Gold Nanostructuration in Paper-based Electrodes. (2017) - Nunez-Bajo, E.; Blanco-Lopez, M.C.; Costa-García, A.; Fernández-Abedul, M.T.
Abstract: Simple and inexpensive strategies to enhance the electrochemical properties of carbon and gold-sputtered Paper-Working-Electrodes (PWE) disks were developed through gold nanoparticles (AuNPs)electrogenerated from AuCl4 − solutions by chronopotentiometry or cyclic voltammetry. In order to ensure a good connection, the wax-defined paper area was adhered to the working electrode of a conventional screen-printed electrode (SPCE) that allows the use of the reference and auxiliary electrodes. Nanostructured paper-based electrodes were characterized by Scanning Electron Microscopy (SEM). Possibilities of use for As(III) determination in wines were also evaluated.